FENOMENA DESA PERBATASAN DI SAJINGAN BESAR STUDI KASUS TENTANG KOORDINASI DALAM PELAKSANAAN PROGRAM KOTA TERPADU MANDIRI DI DESASEBUNGA KECAMATAN SAJINGAN BESAR KABUPATEN SAMBAS PROVINSIKALIMANTAN BARAT - E.01108016, Abelnus (FISIP Universitas Tanjungpura, 2014)
The most fundamental problem that arises in the construction of the center of the Integrated Programme in Rural Independent Sebunga is unclear from the government budget, good budget comes from central government, or local governments. So the researchers found that the development program in the field of Integrated City Independent Sebunga village that has been implemented is not realized, or can be said as the program fails. No realization of the Independent Program Integrated City, due to several factors one of which budget factors, socialization, coordination and management authority. The program is said to fail in practice, because it is not in accordance with the initial plan as in the Master Program of Integrated Independent City in the year 2011. Based on background research, then that becomes the formulation of the research problem is: How Process Coordination in Implementing Integrated Urban Programs in Rural Independent Sebunga Subdistrict Sajingan Great Sambas district. The purpose of this study, the following: To find out the situation and condition of infrastructure in the village Sebunga, Knowing Implementation of Integrated Urban Village Independent Sebunga, Knowing the factors that affect the implementation of the Integrated City Independent. Writing this essay, intended want to know Process Coordination in Implementing Integrated Urban Programs in Rural Independent Sebunga. The research method used in this study is a qualitative method of descriptive type of research. For the conclusion of this study is that the Rural Community Sebunga largely rely on land transport, main roads Sebunga village, the rolling hills, building the Integrated Independent Cities Program failed. As for the suggestion is recommend that the government allocate sufficient budget, ongoing socialization, the Government should provide infrastructure roads, clear delegation of authority from central government to the provincial and district governments Sambas.Â Keywords: Coordination, Implementation, Program Integrated City Independent